A space‐based, high‐resolution view of notable changes in urban NOx pollution around the world (2005–2014). Issue 2 (20th January 2016) - Duncan, Bryan N.; Lamsal, Lok N.; Thompson, Anne M.; Yoshida, Yasuko; Lu, Zifeng; Streets, David G.; Hurwitz, Margaret M.; Pickering, Kenneth E.
Abstract: Nitrogen oxides (NOx = NO + NO2 ) are produced during combustion processes and, thus may serve as a proxy for fossil fuel‐based energy usage and coemitted greenhouse gases and other pollutants. We use high‐resolution nitrogen dioxide (NO2 ) data from the Ozone Monitoring Instrument (OMI) to analyze changes in urban NO2 levels around the world from 2005 to 2014, finding complex heterogeneity in the changes. We discuss several potential factors that seem to determine these NOx changes. First, environmental regulations resulted in large decreases. The only large increases in the United States may be associated with three areas of intensive energy activity. Second, elevated NO2 levels were observed over many Asian, tropical, and subtropical cities that experienced rapid economic growth. Two of the largest increases occurred over recently expanded petrochemical complexes in Jamnagar (India) and Daesan (Korea). Third, pollution transport from China possibly influenced the Republic of Korea and Japan, diminishing the impact of local pollution controls. However, in China, there were large decreases over Beijing, Shanghai, and the Pearl River Delta, which were likely associated with local emission control efforts. Fourth, civil unrest and its effect on energy usage may have resulted in lower NO2 levels in Libya, Iraq, and Syria. Fifth, spatial heterogeneity within several megacities may reflect mixed efforts to cope with air quality degradation. We also show the potential of high‐resolution data for identifying NOx emission sources in regions with a complex mix of sources. Intensive monitoring of the world's tropical/subtropical megacities will remain a priority, as their populations and emissions of pollutants and greenhouse gases are expected to increase significantly. Key Points: Notable changes in NO2 levels globally and their causes over last decade High‐resolution OMI NO2 data show large spatial heterogeneity in world's megacities There is a strong need to develop observational networks in tropics and subtropics